2018
DOI: 10.1016/b978-0-444-63916-5.00003-3
|View full text |Cite
|
Sign up to set email alerts
|

Gravity estimation and verticality perception

Abstract: Gravity is a defining force that governs the evolution of mechanical forms, shapes and anchors our perception of the environment, and imposes fundamental constraints on our interactions with the world. Within the animal kingdom, humans are relatively unique in having evolved a vertical, bipedal posture. Although a vertical posture confers numerous benefits, it also renders us less stable than quadrupeds, increasing susceptibility to falls. The ability to accurately and precisely estimate our orientation relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 152 publications
1
46
0
1
Order By: Relevance
“…Amongst others, one of these solutions is to learn and store internal models to disambiguate sensory information and to predict forthcoming movement dynamics. On earth, a pervasive component affecting perception and motion is gravity (Bringoux et al, 2012; Dakin and Rosenberg, 2018; Elmore et al, 2014; Gaveau et al, 2011, 2016; Jorges and Lopez-Moliner, 2017; Klein et al, 2018; Lacquaniti et al, 2013; McIntyre et al, 2001; Van Pelt et al, 2005; Rosenberg and Angelaki, 2014; Saradjian et al, 2014; La Scaleia et al, 2019; Senot et al, 2005; Tajadura-Jimenez et al, 2018; De Vrijer et al, 2008). Studies in both humans and non-human primates have provided strong evidence that the brain evolved an internal representation of gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst others, one of these solutions is to learn and store internal models to disambiguate sensory information and to predict forthcoming movement dynamics. On earth, a pervasive component affecting perception and motion is gravity (Bringoux et al, 2012; Dakin and Rosenberg, 2018; Elmore et al, 2014; Gaveau et al, 2011, 2016; Jorges and Lopez-Moliner, 2017; Klein et al, 2018; Lacquaniti et al, 2013; McIntyre et al, 2001; Van Pelt et al, 2005; Rosenberg and Angelaki, 2014; Saradjian et al, 2014; La Scaleia et al, 2019; Senot et al, 2005; Tajadura-Jimenez et al, 2018; De Vrijer et al, 2008). Studies in both humans and non-human primates have provided strong evidence that the brain evolved an internal representation of gravity.…”
Section: Introductionmentioning
confidence: 99%
“…We further found that 567 choice activity was preferentially carried by neurons which robustly represented the task-relevant 568 sensory information, and that the strength of choice activity increased with sensory tolerance. The 569 extent to which subcortical vestibular neurons resolve the gravito-inertial acceleration ambiguity 570 necessary to represent translation independent of head tilt (Dakin and Rosenberg, 2018) similarly 571 correlates with the strength of choice activity (Liu et al, 2013). Across modalities, these results 572 reveal that neurons which have resolved fundamental ambiguities about the sensory information 573 that an animal is actively discriminating preferentially carry choice activity.…”
Section: Potential Origins Of Choice-related Activity 559mentioning
confidence: 91%
“…The mean () and concentration () parameters describe the accuracy and precision of perception, respectively (Murray and Morgenstern, 2010;Seilheimer et al, 2014;Dakin and Rosenberg, 2018). The closer is to 0, the more accurate (less biased) the judgments.…”
Section: Quantifying Tilt Perceptionmentioning
confidence: 99%